Japan's concessions towards trade fairness: Mistaken western views - Radha Sinha (Intereconomics, 1982)
It is now acknowledged even by US officials that Japan's recent efforts to liberalize trade have been remarkable. Our author, who has recently published a book on “Japan's Options for the 1980s”, argues that the continuing EEC complaints about Japan's behaviour as a trading partner are unjustified: Japan is simply being made a scapegoat for the EEC's own failures.
Keywords: 330; World Trade